Incidental extra-cardiac pathologies on cardiac computed tomography - Malik, Amna; Khan, Basma (Journal of Fatima Jinnah Medical University, 2020)
Extracardiac pathologies are frequently present in cardiac CT but are not routinely commented upon, and sometimes may have serious medical concern. This study aims to identify extracardiac pathologies present in patients undergoing cardiac computed tomography (CT) for some cardiac reasons. Patients and Methods: This six months cross sectional study was conducted in the Department of Diagnostic Radiology in collaboration with Department of Cardiology, Punjab Institute of Cardiology Lahore. Total 200 patients from Jan to June 2017 referred to Radiology department for Cardiac CT were evaluated for extracardiac manifestations, including insignificant incidental findings and normal variants. The data was entered into SPSS version 20 and simple percentages were calculated. Results: In this study, out of total 200 patients, 61% of the patients had extra cardiac pathologies. Most common extra cardiac findings included lung pathologies (63%), hepatic diseases (11%), mediastianal pathologies (9%), pulmonary embolism (4%), aortic dissection (4%), bone abnormalities (3%), breast diseases (2%), adrenal diseases (2%) and normal anatomical variants (2%). Conclusion: On the basis of findings of this study, it is concluded that there is a high percentage of non-cardiac pathologies in patients undergoing CT for cardiac assessment. It is therefore suggested that the radiologists should routinely report and emphasize any significant incidental extracardiac pathology and cardiologists should consider these findings for an optimal patient outcome